Decadal trends of maternal mortality and utilization of maternal health care services in India: Evidence from nationally representative data - Ravleen Kaur Bakshi; Neeta Kumar; Arti Srivastava; Sonam Kumari; Pradeep Aggarwal; Md Asif Khan; Khangembam Jitenkumar Singh (Journal of Family Medicine and Primary Care)
Introduction: The Sustainable Development Goals (SDGs) aim to reduce the global maternal mortality ratio (MMR) to less than 70 maternal deaths per 100,000 live births by 2030. In India, the MMR has significantly declined over the years and currently stands at 97 per 100,000 live births. Despite this achievement, accurately estimating maternal mortality remains a challenge, mainly because of incomplete records of maternal deaths and their causes. This study aims to review national trends in maternal mortality, using data from the Sample Registration System (SRS) and National Family Health Survey (NFHS). Additionally, it explores the relationship between improvements in the utilization of maternal healthcare services and their impact on reducing maternal mortality. Material and Methods: The study examines trends in maternal mortality using nationally available datasets such as the SRS, NFHS, National Sample Survey, and government administrative records. These publicly available sources provide insight into maternal healthcare utilization patterns over time. Key indicators analyzed include antenatal care (four or more visits), skilled birth attendance, and postnatal care utilization. Additionally, secondary sources like the World Health Report were reviewed for historical context. Results: India has achieved a remarkable decline in MMR over the past three decades, dropping from 570 maternal deaths per 100,000 live births in 1990 to 103 in 2019–2020 and further to 97 in 2023. Historically, the MMR was much higher, with 1,287 maternal deaths per 100,000 live births recorded in 1957. The following decades witnessed a steady reduction: 1,355 in 1960, 892 in 1970, 437 in 1991, 327 in 2000, 212 in 2009, and 130 in 2015. A recent decline of 8.8% was observed between 2016 and 2018 (MMR: 113) and 2020 (MMR: 103). Concurrently, maternal healthcare utilization demonstrated significant improvement, with upward trends in antenatal care, institutional deliveries, and postnatal care across the country. Conclusion: The consistent decline in India’s MMR is because of improvements in socioeconomic conditions, healthcare infrastructure, and public health initiatives such as Janani Suraksha Yojana and Pradhan Mantri Surakshit Matritva Abhiyan. Enhanced transport networks, mobile communication, and rural infrastructure have improved access to maternal care, while grassroots workers such as Accredited Social Health Activists have strengthened antenatal and postnatal service delivery. However, direct obstetric causes like hemorrhage, infection, and sepsis still significantly contribute to maternal deaths. Achieving the SDG target of 70 maternal deaths per 100,000 live births by 2030 requires addressing regional disparities, strengthening health systems, and overcoming resource constraints. Closing gaps in maternal healthcare utilization and fostering collaboration among stakeholders is critical for implementing sustainable and equitable health reforms.